2007
DOI: 10.1111/j.1469-8749.2007.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement of the Gross Motor Function Classification System in an ambulant population of children with cerebral palsy

Abstract: Gross Motor Function Classification System (GMFCS) level was reported by three independent assessors in a population of children with cerebral palsy (CP) aged between 4 and 18 years (n=184; 112 males, 72 females; mean age 10y 10mo [SD 3y 7mo]). A software algorithm also provided a computed GMFCS level from a regional CP registry. Participants had clinical diagnoses of unilateral (n=94) and bilateral (n=84) spastic CP, ataxia (n=4), dyskinesia (n=1), and hypotonia (n=1), and could walk independently with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 28 publications
6
43
3
2
Order By: Relevance
“…Indexes of agreement quite similar to the students' group of this research (Group 3) were obtained in other studies, but with more experienced professionals 8,10,12,23 . The study of Kondo et al 10 involved professionals from different areas (physical therapists, occupational therapists, speech therapists, doctors, and nurses) who made direct observation of the child, with kappa of 0.66.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Indexes of agreement quite similar to the students' group of this research (Group 3) were obtained in other studies, but with more experienced professionals 8,10,12,23 . The study of Kondo et al 10 involved professionals from different areas (physical therapists, occupational therapists, speech therapists, doctors, and nurses) who made direct observation of the child, with kappa of 0.66.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we found substantial agreement among students (Group 3) or professionals of the same area, with up to two years of experience (Group 2), when they classified the motor level of children using the Brazilian version of the GMFCS E&R. In most studies, the agreement in the classification of the GMFCS has also been substantial, with kappa coefficient raging between 0.64 and 0.80 4,9,12 , involving different health professionals (physical therapists 4,10,12,14,17 , doctors 8,9,10,17 , occupational therapists 4,5 , speech therapists 10 , and nurses 10 ) and different methods of collecting information to classify the gross motor function using the GMFCS or GMFCS E & R (direct observation 4,8,9,12,16 , questioning of parents 12,16 , review of medical records 7,8,23 ). Indexes of agreement quite similar to the students' group of this research (Group 3) were obtained in other studies, but with more experienced professionals 8,10,12,23 .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Based upon the concepts of disability and functional limitation as laid out by the World Health Organization, it classifies children by the level of their motor ability. It is presented as a 5-point ordinal scale in which the higher the level, the less able the child 2) . Formal CP classification methods, such as the GMFCS, have been developed in order to standardize the clinical variability, which is one of the major characteristics of CP 3) .…”
Section: Introductionmentioning
confidence: 99%